Computer applications for selecting operating parameters of stationary grain crop thresher - Olaoye, Joshua Olanrewaju; Oni, Kayode C; Olaoye, Mary M (International Journal of Agricultural and Biological Engineering, 2010)
In this study, various operating parameters influencing performance of stationary grain crop threshers were established. These parameters were deduced from the established analytical models describing the underlying principles for the crop characteristics and machine variables as factors influencing the overall machine performance of a stationary multi-crop thresher. A computer programme written in Visual Basic was used to select optimum operating performance of the threshing process in a stationary tooth–peg grain crop thresher. An IITA-popularized stationary multi-crop thresher was used to test the practical feasibility of the computer based output of the threshing process. A split – split – unit statistical design was used for data collection. The data collected were analyzed using the GENSTAT 5 statistical package with its computer programme. The results showed that graphs of data from measured thresher performance indices against the predicted data for all the established models indicated high correlation between the models and the measured data at p ≤5% significance level. The minimum energy requirements for detachment of sorghum and rice were observed at the threshing cylinder speed of 500 r/min (10.5 m/s) and 615 r/min (13.0 m/s), respectively. The combination of the threshing cylinder speed of 500 r/min (10.5 m/s) and 615 r/min (13.0 m/s) at crop moisture content of 12.8 % and 16.2 % indicated optimum threshing conditions for sorghum and rice, respectively. Keywords: computer applications, grain, models, thresher, performance, simulation DOI: 10.3965/j.issn.1934-6344.2010.03.008-018 Citation: Joshua Olanrewaju Olaoye, Kayode C Oni, Mary M Olaoye. Computer applications for selecting operating parameters of stationary grain crop thresher. Int J Agric & Biol Eng, 2010; 3(3): 8<span style="font-size: 9pt; line-height: 135%; font-family: